El hermano mayor, reflexiones sobre el legado universal de Ricardo Palma - Del Río Donoso, Luis (2018)
Brief biography of politician, diplomat, writer and traditionalist Ricardo Palma, considering the socio-cultural environment, Peru and Latin America, in the second half of the nineteenth century, formative periods of this writer, military training of sailor, politician, the influence of his membership in the Masonic Concordia lodge, but mainly his intellectual formation in Valparaiso Chile and the contact and sharing with intellectuals from this country. The importance of the role he fulfilled as Director of the National Library, after the War of the Pacific, a task that made him his honor in the Beggar Librarian. Finally, he points out the importance of his intellectual work in compiling the popular language and enriching the lexicon of Spanish, from what we now know as a pluricultural approach.